2024
DOI: 10.3390/nu16081161
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effect and Gut Microbiota Modulation by Quercetin, Luteolin, and Xanthohumol in a Rat Model for Colorectal Cancer Prevention

Álvaro Pérez-Valero,
Patricia Magadán-Corpas,
Suhui Ye
et al.

Abstract: Colorectal cancer stands as the third most prevalent form of cancer worldwide, with a notable increase in incidence in Western countries, mainly attributable to unhealthy dietary habits and other factors, such as smoking or reduced physical activity. Greater consumption of vegetables and fruits has been associated with a lower incidence of colorectal cancer, which is attributed to their high content of fiber and bioactive compounds, such as flavonoids. In this study, we have tested the flavonoids quercetin, lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Pharmacological research has shown that it has anti-virus, anti-bacteria, anti-oxidative, anti-inflammatory, anti-dermatitis, gastro-protective, and anti-cancer effects, mainly due to the presence of essential oils, flavonoids, and organic acids [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Pharmacological research has identified various anti-cancer components of Aiye, including jaceosidin, irigenin, luteolin, eriodictyol, apigenin, eupatilin, casticin, and artemetin [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In obesity, the secretion of adipokines by adipose tissue was dysregulated, characterized by the up-regulation of proinflammation adipokines and the down-regulation of anti-inflammation adipokines [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological research has shown that it has anti-virus, anti-bacteria, anti-oxidative, anti-inflammatory, anti-dermatitis, gastro-protective, and anti-cancer effects, mainly due to the presence of essential oils, flavonoids, and organic acids [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Pharmacological research has identified various anti-cancer components of Aiye, including jaceosidin, irigenin, luteolin, eriodictyol, apigenin, eupatilin, casticin, and artemetin [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In obesity, the secretion of adipokines by adipose tissue was dysregulated, characterized by the up-regulation of proinflammation adipokines and the down-regulation of anti-inflammation adipokines [ 30 ].…”
Section: Introductionmentioning
confidence: 99%